Biotransformation, endocrine, and genetic responses of Anguilla anguilla L. to petroleum distillate products and environmentally contaminated waters - Pacheco, M. (2001)
The European eel (Anguilla anguilla L.) was exposed to diesel oil water-soluble fraction (DWSF) and gasoline water-soluble fraction (GWSF). The potential of these fractions to induce endocrine disruption, carbohydrate, and xenobiotic metabolism effects, as well as genotoxic responses, was investigated in a time-course laboratory study (3 h to 6 days). Both water-soluble fractions induced a time-related increase in liver ethoxyresorufin-O-deethylase (EROD) activity, as well as the appearance of erythrocytic nuclear abnormalities (ENA) after a 6-day exposure, revealing its genotoxic properties. Initially, DWSF exposure revealed an inhibition of the typical stress responses demonstrated by plasma cortisol and lactate decrease. Nevertheless, this effect progressively disappeared, allowing a plasma glucose and lactate increase after 6 days of exposure. Fish exposed to GWSF exhibited a liver alanine transaminase (ALT) activity increase after a short exposure while the longest exposure revealed liver damage expressed as an ALT activity decrease. A field caging experiment, carried out in a harbor area (Aveiro Lagoon, Portugal), and a complementary laboratory experiment were designed to assess the influence of the daily tide dynamic on polyaromatic hydrocarbon water distribution and effects on liver EROD and ALT activities, as well as ENA frequency. Eels exposed to low- and high-tide harbor waters, in the laboratory, exhibited a similar degree of genotoxicity, whereas clear differences were observed as EROD induction. In the field experiment, caged eels did not display significant responses enhancing the relevance of natural environmental factors on toxicity mechanisms as well as on the apparent lack of toxicity in harbor waters.